Asean Modern Leadership Styles: A Critical Analysis - Gumilar, Ruly; Widodo, Pujo; Ayu Elita Hafizah, Mas (CV. Publikasi Indonesia, 2022)
The countries that are members of ASEAN have a vision to create regional stability both politically, economically as well as defense and security. Strategic location of ASEAN countries, world geopolitical and geoeconomic dynamics, shifting of world power maps and conflicts of interest. This condition has the potential to make ASEAN the axis of the world, but ASEAN countries are not geographically integrated, so that the geopolitical position of each member country is different and different levels of economy have an impact on the implementation of an agreement. The importance of strategic leadership in ASEAN with a dynamic and visionary modern leadership style is needed to be able to maintain stability in the ASEAN region, as well as make a new axis of world power. The future of ASEAN is not only influenced by the leadership style of the ASEAN Chair, but is also influenced by the Leadership Style of ASEAN member countries, the ASEAN Leadership Style in recent years does not seem to have a significant impact. Based on the consideration of the different conditions of ASEAN members, the Modern Leadership Style: Adaptive and Visionary, can be applied by the ASEAN Chair, so that ASEAN's functions and roles are more optimal.